Balancing the educational choices in the decisionmaking of a dean of medicine: Fission or fusion - Jacqueline Wolvaardt; B Lindeque; Pieter du Toit (South African Medical Association, 2016)
Background. The literature on deans of medicine focuses mostly on the qualifications, roles, abilities, management and leadership competence of the deans. The gap between theory and practice is, however, the nucleus of the position. Objectives. To describe insights into the educational forces that act on a dean of medicine and the implications for those who wish to bring about change â€" in this case, changes in the inclusion of public health in the medical curriculum. Methods. A series of in-depth interviews of a vice dean (VD) of medicine was conducted over a period of a year. The interviews were transcribed. Initial in-depth analysis of the transcriptions was done using open coding, prior to a second round of coding that resulted in themes. Results. The interviews revealed a serendipitous aspect, namely the ontological realities of the VDâ€™s practice. This practice is characterised by balancing multiple internal and external forces, such as the breadth and depth of the curriculum that acts on the medical curriculum. Conclusion. The ontological realities of the VD bring to life the qualifications and leadership, and management competence, roles and abilities described in the literature. The multiple â€" often opposing â€" educational choices that deans face are an inescapable reality of deanship. Medical deans must balance these opposing forces to ensure fusion within the curriculum, and those interested in changes, such as strengthening the teaching of public health in this curriculum, need to plan on how to overcome this.